EFFECT OF BREAKFAST SKIPPING ON BODY MASS INDEX IN ADOLESCENT UNIVERSITY GIRLS - Noor Fatima; Zirwa Noor; Swaira Shafique (Journal of University Medical & Dental College, 2020)
ABSTRACTBACKGROUND & OBJECTIVE:  Breakfast is considered as important meal of the day and it should provide 25 % of total energy intake including all five food groups. Breakfast skipping is common in adolescents and it is associated with changes in Body Mass Index (BMI) and cognitive abilities. Breakfast skipping enhances appetite throughout the remaining day which leads to over eating resulting in overweight and obesity. Addition of breakfast is useful plan of action to improve satiety, reduced food motivation and improve diet quality. Eating breakfast regularly has association between both with less mental distress and healthy life style. For this purpose, this study was designed to determine the prevalence of breakfast skipping in adolescent’s university girls and its effect on their Body Mass Index (BMI). METHODOLOGY: For the current research, 200 individuals were selected from different departments of The University of Faisalabad. Questionnaire was developed and height, weight and dietary history were measured. The data obtained from the study was tabulated and statistically analyzed by applying Analysis of Variance (ANOVA) and Least Significant Difference (LSD).RESULTS: Skipping of breakfast has significant effect on increasing the Body Mass Index (BMI) in university adolescent girls.CONCLUSION: Breakfast skipping resulted in increased BMI in university adolescent girls.